2014
DOI: 10.1063/1.4879777
|View full text |Cite
|
Sign up to set email alerts
|

Massively parallel molecular dynamics simulation of formation of clathrate-hydrate precursors at planar water-methane interfaces: Insights into heterogeneous nucleation

Abstract: The formation of methane-hydrate precursors at large planar water-methane interfaces has been studied using massively parallel molecular dynamics in systems of varying size from around 10 000 to almost 7 × 10(6) molecules. This process took two distinct steps. First, the concentration of solvated methane clusters increases just inside the aqueous domain via slow diffusion from the methane-water interface, forming "clusters" of solvated methane molecules. Second, the re-ordering process of solvated methane and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 48 publications
4
46
1
Order By: Relevance
“…56 Finally, Vatamanu and Kusalik 22 have shown that local fluctuations of solute concentration beyond the equilibrium value might enhance nucleation. Analogous effects have also been observed in other clathrates (see, for example, ref 40).…”
Section: Resultsmentioning
confidence: 98%
“…56 Finally, Vatamanu and Kusalik 22 have shown that local fluctuations of solute concentration beyond the equilibrium value might enhance nucleation. Analogous effects have also been observed in other clathrates (see, for example, ref 40).…”
Section: Resultsmentioning
confidence: 98%
“…31,38 Despite the clear underlying limitations of such a 'coarse-grained' potential, such a simple model has a potentially clear and valuable contribution for hydrate simulation, and it has established their value for equilibrium simulation of methane hydrates 31 and methane-water interfaces. 39 In any event, re-parameterisng coarse-grained models such as mW and a single-particle variant of TIP5P to and mTIP4P/2005REM 40 may offer similar greater accuracy than commonly used atomistic models such as SPC/E at only a hundredth of the computational cost. 40 mW-type coarse grained models truncate after three body…”
Section: Introductionmentioning
confidence: 99%
“…1,2 A unit cell in sII hydrate consists of 136 water molecules forming sixteen small 5 12 cages and eight large hexadecahedral 5 12 6 4 cages. 1,2 In recent years, the molecular simulation of clathrate hydrates has revealed much about their structural properties, 3 and Monte Carlo 4 and molecular dynamics (MD) simulations, whether brute force (i.e., standard) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] or biased, [22][23][24][25] of hydrate formation have revealed a propensity for either (approximately) sI or sII polymorphs to form, despite one form typically being most thermodynamically stable for a given guest type (and temperature/pressure). Given that such simulation can provide molecular-level insights into hydrate-formation dynamics, this allows for probing the structural nature of the growing hydrate a) Authors to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%